2014
DOI: 10.1371/journal.pone.0088721
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Depressive Disorder following Non-Alcoholic Cirrhosis: A Nationwide Population-Based Study

Abstract: Background & AimsTo evaluate the risk of depressive disorders among non-alcoholic patients by using the Taiwan National Health Insurance Research Database (NHIRD).MethodsWe conducted a retrospective study of a matched cohort of 52 725 participants (10 545 non-alcoholic cirrhotic patients and 42 180 control patients) who were selected from the NHIRD. Patients were observed for a maximum of 11 years to determine the rates of newly onset depressive disorders, and Cox regression was used to identify the risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This finding was in contrast with previous studies [ 24 , 34 , 35 ]. Perng et al reported that non-alcoholic cirrhotic patients had higher risk to develop depressive disorders than patients without cirrhosis (incidence risk ratio 1.76, 95% CI, 1.57–1.98, P<0.001) [ 18 ]. Further studies will need to investigate the subsequent depression in HCC patients with non-alcoholic cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was in contrast with previous studies [ 24 , 34 , 35 ]. Perng et al reported that non-alcoholic cirrhotic patients had higher risk to develop depressive disorders than patients without cirrhosis (incidence risk ratio 1.76, 95% CI, 1.57–1.98, P<0.001) [ 18 ]. Further studies will need to investigate the subsequent depression in HCC patients with non-alcoholic cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only those having at least three consecutive corresponding diagnoses were designated as having depressive disorder for better diagnostic validity. For preventing confounding effects, we followed a flowchart of a previous study [ 18 ] and excluded patients with bipolar disorders (ICD-9-CM code: 296.0, 296.1, 296.4, 296.5, 296.6, 296.7, 296.8, 296.80, and 296.89), or alcohol-use disorders (ICD-9-CM codes: V113, 9800, 2650, 2651, 3575, 4255, 3050, 291, 303, and 571.0–571.3) because higher rate of impaired liver function due to mood stabilizers such as valproate, carbamazepine, or alcohol use [ 15 ]. All patients with HCC were observed until diagnosed with depressive disorders according to ICD-9-CM codes (ICD-9-CM code: 296.2X-296.3X, 300.4, and 311.X), death, or withdrawal from the NHI system, or December 31, 2007.…”
Section: Methodsmentioning
confidence: 99%
“…Monthly income was grouped into low income (monthly income b 20,000 New Taiwan Dollar [NTD]), medium income (20,000 NTD ≤ monthly income b 40,000 NTD), and high income (monthly income ≥ 40,000 NTD) [21]. The study end point was the occurrence of dementia (ICD-9-CM codes: 290.0-290.4, 331.0) during the follow-up period [15].…”
Section: Study Populationmentioning
confidence: 99%
“…13 Information about the degree of urbanization (urban, suburban, or rural) of each patient was available in the Taiwan NHIRD on the basis of the townships where the patients lived. The stratifications of townships were based on the township population density (people per 1 ), population ratio of people with educational levels of college or above, population ratio of people >65 years of age, population ratio of agriculture workers, and the number of physicians per 100 000 people (http://ntur.lib.ntu.edu.tw/bitstream/246246/176519/1/5.pdf).…”
Section: Definitions Of Rate-control Treatments and Study End Pointmentioning
confidence: 99%